Investigation of Cracking in Reinforced Concrete Structures by Means of Standardized Deformation Models - Mikhail V. Morgunov; Anzhelika A. Lyudkevich (Железобетонные конструкции, 2023)
In this study, a detailed analysis of the use of standardized deformation models is carried out to calculate the design characteristics of reinforced concrete elements, such as crack resistance. For theoretical verification of the values of the moment of cracking, calculation methods based on the use of a nonlinear deformation model are used.A theoretical study of cracking moment using a non-linear deformation model shows that the application of a two-line diagram of concrete deformation allows to obtain the most accurate values of cracking moment.